Acute Disseminated Encephalomyelitis with Measles (Journal of Enam Medical College, 2013)
Acute disseminated encephalomyelitis is an inflammatory demyelinating illness usually associated with infections or antecedent immunization. Due to control of most vaccine preventable diseases in developed countries, most cases of acute disseminated encephalomyelitis occur in developing countries and are seen secondary to nonspecific upper respiratory tract infections. We report a case of acute disseminated encephalomyelitis associated with measles in a 2½-year-old male child despite having measles vaccination in infancy. The diagnosis was based on clinical findings and CT scan of brain. The patient was managed with high dose corticosteroids along with supportive measures. He recovered completely and follow-up for six months revealed no neurological deterioration. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13875 J Enam Med Col 2013; 3(1): 50-52